Reflective practice framework for TESOL teachers: one teacher's reflective journey. Issue 1 (2nd January 2019) - Farrell, Thomas S.C.; Kennedy, Brennand
ABSTRACT: Just as in the field of general education, scholars within the field of teaching English to speakers of other languages (TESOL) have also struggled to come to a consensus as to how reflective practice should be operationalized with many different approaches suggesting a retrospective approach to questioning about practice. As a result, many of these approaches have led to a type of routinization of reflection. Worried about such routinization of reflection, Farrell developed a more holistic approach to reflective practice that recognizes the spiritual, moral, and emotional aspects of reflection, as well as the usual retrospective questions about practice. This paper outlines a case study of the reflections of one experienced TESOL teacher teaching in South Korea using Farrell's framework for reflecting on practice that included reflections on his philosophy, principles, theory, practice, and beyond practice. The results revealed three common themes of approachability, art-oriented conceptions, and curiosity that emerged in all aspects of his reflection as uniquely influential parts of a larger whole. Thus, Farrell's holistic framework for teacher reflection employed in this study provided multiple filters through which these various parts could be viewed.